Catalogue of the family Psychidae in China (Lepidoptera: Tineoidea) - Qian-Ju Jia; Chun-Sheng Wu (SHILAP)
This catalogue of Psychidae in China is piled based on a literature research in multiple languages and on the study of Psychidae specimens in National Zoological Museum of China and Natural History Museum in London. Prior our research, less than 20 Psychidae species are listed in China, however we expand the list to 59 species, 35 genera and 7 subfamilies, among them, two species are newly recorded in China.